Efficacy and safety of intravenous immunoglobulin with rituximab versus rituximab alone in childhood-onset steroid-dependent and frequently relapsing nephrotic syndrome: protocol for a multicentre randomised controlled trial. Issue 9 (23rd September 2020) - Hogan, Julien; Perez, Aubriana; Sellier-Leclerc, Anne-Laure; Vrillon, Isabelle; Broux, Francoise; Nobili, Francois; Harambat, Jerome; Bessenay, Lucie; Audard, V; Faudeux, Camille; Morin, Denis; Pietrement, Christine; et al.
Abstract : Introduction: Guidelines for the treatment of steroid-dependent nephrotic syndrome (SDNS) and frequently relapsing nephrotic syndrome (FRNS) are lacking. Given the substantial impact of SDNS/FRNS on quality of life, strategies aiming to provide long-term remission while minimising treatment side effects are needed. Several studies confirm that rituximab is effective in preventing early relapses in SDNS/FRNS; however, the long-term relapse rate remains high (~70% at 2 years). This trial will assess the association of intravenous immunoglobulins (IVIgs) to rituximab in patients with SDNS/FRNS and inform clinicians on whether IVIg's immunomodulatory properties can alter the course of the disease and reduce the use of immunosuppressive drugs and their side effects. Methods and analysis: We conduct an open-label multicentre, randomised, parallel group in a 1:1 ratio, controlled, superiority trial to assess the safety and efficacy of a single infusion of rituximab followed by IVIg compared with rituximab alone in childhood-onset FRNS/SDNS. The primary outcome is the occurrence of first relapse within 24 months. Patients are allocated to receive either rituximab alone (375 mg/m²) or rituximab followed by IVIg, which includes an initial Ig dose of 2 g/kg, followed by 1.5 g/kg injections once a month for the following 5 months (maximum dose: 100 g). Ethics and dissemination: The study has been approved by the ethics committee (Comité de Protection des Personnes) of Ouest I and authorised by the French drug regulatory agency (Agence Nationale de Sécurité du Médicament et des Produits de Santé). Results of the primary study and the secondary aims will be disseminated through peer-reviewed publications. Trial registration number: NCT03560011 .